Staff awareness level towards Petronas staff Kad Mesra promotions / Suhailie Bakrin - Bakrin, Suhailie (2008)
PETRONAS, the acronym for Petroliam Nasional Berhad, was incorporated on 17 August 1974 under the Companies Act 1965. It is wholly-owned by the Malaysian government and is vested with the entire ownership and control of the petroleum resources in Malaysia through the Petroleum Development Act 1974, an Act of Parliament. PETRONAS through it subsidiary, PETRONAS Dagangan Berhad (PDB) has introduced PETRONAS Staff Kad Mesra as part of their plan in promoting loyalty among the PETRONAS Staff. At PETRONAS, they continue to look for new ways to offer better and more convenient services and benefits to their employees. With that, PDB was introduced the new Kad Mesra programme, a new alliance with Real Rewards™, Malaysia's leading loyalty programme. For PETRONAS staff, they will hold Kad MESRA which is tagged with 'P' (Cardholders).